Creating space for (un)well-being: a longitudinal case study of a wellness-focused startup incubator - Kling, Hanna (2025)
This thesis examines how a well-being and performance program integrated into a startup incubator shapes entrepreneurial well-being. The study draws on interview data collected over one year from entrepreneurs and program staff, reflecting participants’ experiences throughout 1.5 years. Using a qualitative case study approach, the analysis highlights that the program’s most meaningful impact emerged not from its structured activities but the incubator’s transformation into a supportive “lived space” that fostered open dialogue, reflection, and awareness of both well-being and ill-being. By embedding the program into the incubator’s daily operations, well-being became normalized and part of the entrepreneurial culture, even for those not actively seeking support. The findings suggest that incubators may effectively support entrepreneurial well-being by prioritizing a supportive space rather than relying solely on structured interventions. This study contributes to research on entrepreneurial support and well-being by emphasizing the importance of organizational space and cultural integration in promoting sustainable entrepreneurship.